Efficacy of Surgical Tenodesis for Treatment of Distal Semitendinosus Hamstring Tendon Injuries. Issue 10 (11th October 2021) - Thompson, Joshua W.; Plastow, Ricci; Kayani, Babar; Baawa-Ameyaw, Joanna; Moriarty, Peter; Asokan, Ajay; Haddad, Fares S.
Background: Understanding the optimal management of distal semitendinosus hamstring injuries is critical for reducing pain, restoring preinjury function, maintaining knee stability, improving hamstring muscle strength, and minimizing the risk of complications and recurrence. To our knowledge, the outcomes of surgical tenodesis for distal semitendinosus hamstring injuries have not been previously reported. Hypothesis: Surgical tenodesis for injuries of the semitendinosus would enable return to preinjury level of sport with low risk of recurrence. Study Design: Case series; Level of evidence, 4. Methods: This prospective single-surgeon study included 13 professional athletes (12 men, 1 woman; mean age, 32 ± 8.2 years; mean body mass index, 26.7 ± 3.9 kg/m 2 ) undergoing treatment for distal semitendinosus hamstring injuries with primary tenodesis to the distal semimembranosus. Indications for surgical tenodesis included distal semitendinosus tendon avulsion injury (n = 8) or residual tendon instability and hamstring weakness after semitendinosus graft harvest for anterior cruciate ligament reconstruction (n = 5). All study patients underwent a standardized postoperative rehabilitation program. The primary outcome was defined as time for return to sporting activity. Secondary outcomes were patient satisfaction, injury recurrence, and complications. The mean follow-up time was 17 months (range, 12-24 months) from date of surgery. Results: All study patients returned to their preinjury level of sporting activity. The mean time from the surgical intervention to return to full sporting activity was 15 ± 4.6 weeks. At 1-year follow-up, all study patients were still participating at their preinjury level of sporting activity, and 12 patients (92%) were very satisfied and 1 patient (8%) was satisfied about the outcomes of their surgery. No study patients had recurrence of the primary injury. No surgical complications, injury recurrence, or reoperations were observed within the follow-up period. Conclusion: Early return to sporting activity was seen after surgical tenodesis for distal semitendinosus hamstring injuries after acute trauma or residual symptoms following previous hamstring graft harvest, with high levels of patient satisfaction and low risk of recurrence at short-term follow-up.